WATER HOLDING CAPACITY AND HEAT TRANSFER ASPECTS OF A MIXTURE OF SUGAR CANE BAGASSE AND WHEAT BRAN IN A PARTIALLY FILLED ROTATING DRUM - Tada, Erika F. R. [UNESP]; Agudelo, Lina M. G.; Thomeo, Joao C. [UNESP] (Brazilian Soc Chemical Eng, 2019)
Maximum water holding capacity of a mixture of sugarcane bagasse and wheat bran was determined in static conditions and in a drum rotated at 1 rpm. The variables filling degree, water flow rate, volume of added water and number of sprinklers were tested to control the moisture content of the solid and the number of rotations to achieve homogeneous moisture content. None of the selected variables was significant, giving the apparatus high flexibility to control moisture content. For the heat transfer experiments, the tested variables were introduction of air through an inner tube amidst the particles, water sprinkling over the bed and drum rotation. The selected variables represented limited mechanisms of heat removal, although efficient when coupled with the drum rotation. The results are of value to control the temperature and the moisture content in solid-state cultivation bioreactors.
Keywords: Rotating drum; Solid-state cultivation; Sugar cane bagasse; Water holding capacity; Heat transfer